2020
DOI: 10.3389/fnut.2020.00068
|View full text |Cite
|
Sign up to set email alerts
|

Overuse of Non-caloric Sweeteners in Foods and Beverages in Chile: A Threat to Consumers' Free Choice?

Abstract: The prevalence of obesity among Chilean adults and children is one of the highest worldwide. To fight the constant increase of non-communicable diseases and the growing sales of sugar-sweetened beverages, the Chilean government recently enacted a new Law of Food Labeling and Advertising imposing the application of front-of-package warning labels in foodstuffs whose composition exceeds limits for critical nutrients including sugar. Accordingly, food companies have been reformulating their products, incorporatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 38 publications
7
43
1
Order By: Relevance
“…Most beverages with added LNCS contained more than one LNCS, and only sucralose and steviol glycosides were used as sole sweetener. A similar finding was presented in the study from Chile [ 15 ]. One of the main reasons for this could be the taste of intensive sweeteners, which tend to have metallic or bitter after taste.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Most beverages with added LNCS contained more than one LNCS, and only sucralose and steviol glycosides were used as sole sweetener. A similar finding was presented in the study from Chile [ 15 ]. One of the main reasons for this could be the taste of intensive sweeteners, which tend to have metallic or bitter after taste.…”
Section: Discussionsupporting
confidence: 90%
“…This indicates a slight, but non-significant ( p = 0.12) increase in the use of LNCS, over the course of two years. Comparison of our results with similar studies showed that the use of LNCS in non-alcoholic beverages in Slovenia was relatively low when compared to Latin America (>40%) [ 15 ], USA (23.9%) [ 26 ], or Spain (39.2%) [ 10 ]. A lower prevalence of LNCS use in non-alcoholic beverages has been reported only for New Zealand (8.7%) and Australia (2.3%) [ 26 ].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…implementation, a decrease in the content of nutrients of concern was observed, but the use of other sweeteners increased. 48 According to the Chilean criteria proposed, most of the SSBs had excessive sugar;…”
Section: Discussionmentioning
confidence: 99%
“…Both approaches should reduce obesity and risk for type 2 diabetes in adults, but uncertainties around long-term health consequences of NNS for children have prompted concerns about potential overuse of NNS in reformulation. [39] It should be noted though that neither SSBs nor beverages containing NNS are recommended for children. [40,41]…”
Section: Ssbs Taxation Reduces Consumption and Purchasing Of Ssbsmentioning
confidence: 99%